Manifestation of risk factors in the development of diabetes mellitus among young people - Gurska, Kateryna; Karpenko, Olena; Ostashevska, Tetiana; Krasiuk, Irina (The Ukrainian Scientific Medical Youth Journal)
this study aims to identify lifestyle risk factors for diabetes in 208 young people from 16 different countries, 50,5% of these respondents are predisposed to diabetes mellitus. FINDRISC and Mayo Clinic recommendations were taken into account. The results of the survey are based on the answers of an anonymous survey, which included groups of questions about general data, anthropometric data, nutrition, physical activity, rest mode, bad habits, heredity and anamnesis. The most critical changes were detected in the consumption of fresh fruits and vegetables (55% do not consume enough), as well as activity and rest mode (67% do not perform physical activity regularly, 47.1% of respondents do not spend the required 7-9 hours on sleep). A comparative analysis of respondents of different origins (Ukrainians and Indians) found that among the representatives of India is more elevated body mass index and increased waist circumference. In addition, the proportion of respondents who have ever had a rise in blood glucose is higher among Indians than among Ukrainians (11,4% vs. 6,8%). There are more respondents in Ukraine who do not exercise regularly than in India.